Agama, Modal Sosial dan Ketahanan Masyarakat dalam Menghadapi Bencana di Kota Banda Aceh - Fajri M Kasim; Abidin Nurdin; M Rizwan (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2021)
This article examines religion as social capital in realizing resilience in Aceh. The purpose of this research is to discuss how religion and its values become social capital, and how to socialize these religious values in society. This research is a qualitative research procedure that produces descriptive data in the form of written or spoken words from observable people's behavior. The theory used is social capital which believes that religious values, norms and beliefs contained in social structures and structures are able to bond and integrate society to move together to solve problems. The approach is ethnography, which is a written description of people's way of life. There are three data techniques, namely; interviews, observation and document study, then analyzed by exclusion, namely matching all data that has been obtained. The results showed that religion is capable of being a social capital, as well as having values and the norms of tawhid, patience, sincerity, tawakkal and togetherness; These values and norms have been socialized since Islam entered Aceh and continue to be carried out by families and religious leaders through education. Thus, through religion as social capital, it can create resilience in the face of disasters in Acehnese society